Synchronous occurrence of acute lymphoblastic leukemia and wilms tumor in two patients: underlying etiology and combined treatment plan. Issue 5 (15th November 2016) - Yi, Joanna S.; Kamihara, Junne; Kesselheim, Jennifer C.; Davies, Kimberly; van Hoff, Jack; Silverman, Lewis B.; Mullen, Elizabeth A.
Abstract: Synchronous cancers are extraordinarily rare in pediatric patients and present a therapeutic challenge. Patient A presented with synchronous unilateral Wilms tumor (WT) and standard‐risk (SR) B‐precursor acute lymphoblastic leukemia (ALL). Genetic testing revealed bialleleic BRCA2/FANCD1 mutations. Patient B, after SR B‐precursor ALL induction therapy, was noted on fever workup to have a renal mass; pathology demonstrated lesion indeterminate between WT and nephrogenic rest. Therapy was customized for each patient to treat both cancers. Both patients have ongoing remission from their cancers, without excessive toxicity. We report two regimens for treating synchronous WT and ALL and recommend screening such patients for cancer predisposition.